FEM analysis of strain distribution in tibia bone and relationship between strains and adaptation of bone tissue - Będziński, Romuald; Ścigała, Krzysztof (Computer Assisted Methods in Engineering and Science, 2023)
The purpose of the research is the estimation of strain distribution in tibia bone. Resultant strain distribution constitutes necessary data for the calculations made in the process of simulation of bone tissue adaptation. Estimation of strain distribution in proximal part of tibia bone is made for different load conditions (including the one following total knee arthroplasty and a surgical correction of lower limb with the application of high tibial osteotomy). The model of tibia bone and soft tissues, prepared for finite element analysis, was made with the use of Ansys 5.6. The geometry of bone was estimated by 3-D digitalisation of a physical model of bone. Displacements distribution obtained from the simulation was compared with the measurements of the physical model of a knee joint. In the research the holographic interferometry method was applied. The results of this calculation are helpful in the estimation of boundary conditions for a simulation of bone tissue functional adaptation in the region of a knee joint. It has been found out that there are differences in strain distribution in different load conditions. However, the perfect agreement of experimental and numerical results for a simple static load indicates that the numerical model is valid for this simulation in a certain range of the applied load.